Comparison of Standard versus Accelerated Ponseti Protocol for Club Foot - Maryam, Nida; Amin, Sohail; Ahmad, Israr; Naz, Kashif Ali; Arif, Qamar; Majeed, Hina (Biological and Clinical Sciences Research Journal, 2025)
Clubfoot (congenital talipes equinovarus) is a common congenital musculoskeletal deformity, and the Ponseti method is the current gold standard for its management. While the standard Ponseti protocol is well-established, accelerated protocols have been introduced to potentially reduce treatment time without compromising outcomes. Objective: To compare the effectiveness of the standard Ponseti protocol versus the accelerated Ponseti protocol in the management of clubfoot. Methods: This quasi-experimental study was conducted at the Pak-Emirates Military Hospital, Combined Military Hospital, Rawalpindi, from April 2024 to February 2025. A total of 144 patients with clubfoot were enrolled and randomly allocated into Group A (standard Ponseti protocol) and Group B (accelerated Ponseti protocol). The Ponseti method was applied as per group allocation, and treatment effectiveness was evaluated using the Pirani scoring system at baseline and at six months follow-up. Data were analyzed using SPSS version 22, with a p-value <0.05 considered statistically significant. Results: Among the 144 patients, the median age was 4.00 (IQR: 1.00–8.00) months, with 92 (63.89%) males and 52 (36.11%) females. The median pre-treatment Pirani score was 5.00 (IQR: 4.00–6.00). At six months, the median post-treatment Pirani score was 1.00 (IQR: 0.00–4.00) in both groups; however, the difference between groups was statistically significant (p=0.005). Treatment effectiveness at six months was higher in the accelerated protocol group (83.33%) compared to the standard protocol group (56.94%) (p=0.001). Conclusion: The accelerated Ponseti protocol demonstrated superior effectiveness compared to the standard protocol for the management of clubfoot, potentially offering faster correction without compromising treatment outcomes.